The Use of An EHR Patient Portal (Mychart-Epic) in Patients With Inflammatory Bowel Disease. Issue 3 (16th October 2019) - Reich, Jason; Canakis, Andrew; Shankar, Divya; Harrington, Jill; Apte, Manisha; Weinberg, Janice; Jones, Eric; Noronha, Ansu; Wasan, Sharmeel K; Farraye, Francis A
Abstract: Introduction: Inflammatory bowel disease (IBD) has a significant effect on patients' overall quality of life (QoL). We hypothesized that an Electronic Health Record (EHR) patient portal (EPIC's Mychart) can be utilized to improve QoL in IBD patients and increase vaccine uptake. Methods: Patients were randomized to receive specific disease (INT) information and to a control arm (CTRL) that received periodic non-IBD related messages. Disease severity was assessed using the Harvey-Bradshaw index, and Simple Clinical Colitis Activity index. QoL was measured using the Short Inflammatory Bowel Disease Questionnaire (SIBDQ). Secondary outcome measures included overall satisfaction with the portal and influenza and pneumococcal vaccine uptake. Results: One hundred twenty-seven patients were randomized: At baseline the CTRL group had a statistically significant higher QoL (Median SIBDQ 53.7) compared with the INT group (median SIBDQ 49.3), P = 0.04. At 6 months, the INT group had a trend towards a significantly greater increase in QoL (median SIBDQ 58) when compared with the CTRL group (median SIBDQ 57.5), P = 0.06. At 6 months more frequent portal use showed a significantly lower median SIBDQ (median 53) compared with patients with less frequent portal use (median 59), P = 0.038. At 6 months 88% of patients felt that the MyChart portal was useful with respect to IBD management. Patients had high rates of portal utilization with one-third of patients logging on weekly, and one-third logging on monthly. With respect to vaccine uptake, both influenza and pneumococcal pneumonia had higher rates of vaccine uptake. Conclusions: Patients showed a trend towards improved QoL after receiving disease-specific information through our EHR portal. A significant increase in vaccine uptake was also seen. Frequent automated messages sent via an EHR portal can improve patient's overall QoL. Larger studies will be needed to determine if automated portal reminders have a significant association with improved QoL, and furthermore to determine if there is any impact on disease activity. Lay Summary: Electronic Health Records (EHRs) are commonly used in practice. In this study, we examined if messages through the EHR improved outcomes. Frequent automated messages sent via an EHR portal improved vaccine rates and may improve quality of life.